Developing a Business Ecosystem for the Creative Culinary Economy in Sukabumi - Supriandi, Supriandi; Ghina, Astri (The Es Economics and Entrepreneurship, 2025)
The culinary industry, as a creative sector of the economy, plays a crucial role in building local economic resilience in Sukabumi City. While it carries great potential, this industry is hampered by continuing issues such as fragmented actor relationships, undeveloped digital infrastructure, a lack of institutional support, and an underdeveloped business ecosystem. This research aims to develop business ecosystem architecture that enables the establishment of an inclusive sustainable food industry through a five-step descriptive qualitative approach: (1) boundary delineation of ecosystems, (2) value mapping of actor roles, (3) value proposition, (4) analysis of interactions, and (5) verification of architecture. Data were collected through in-depth interviews and document review of government, culinary entrepreneur, academic, media, and community stakeholders via the Penta Helix framework. Results show that the existing ecosystem remains structurally uncoordinated and functionally inefficient, particularly in terms of data integration, funding avenues, and service accessibility. Applying the five-step model—establishing ecosystem boundaries, mapping actor roles, value propositions, interaction analysis, and architecture verification—a digitally integrated ecosystem design is proposed in this research. The design emphasizes collaborative governance, digital transformation, and actor orchestration to facilitate effective mobilization of resources, information exchange, and co-creation of value. The results contribute to the literature in business ecosystem models and provide local governments, as well as stakeholders, with practical recommendations for strengthening the culinary creative economy industry.